EVALUATION OF THE POTENTIAL ASSOCIATED FACTORS CONTRIBUTING TO VARIOUS SIDE EFFECTS OF COVID-19 VACCINES IN BANGLADESH - TAMANNA, SAMIHA; GHOSH, RUPALI; REZA, SAKIB; ISLAM, SOJIBUL; KHAN, NOOR MUHAMMAD (International Journal of Applied Pharmaceutics, 2023)
Objective: Due to questions about the safety and possible side effects of COVID-19 vaccines, initially, most individuals with chronic comorbid conditions showed unwillingness to vaccination. Though COVID-19 vaccines were found safe in clinical trials, real-world results still need to be explored to generate and further analyze the safety and efficacy profile of these vaccines. Our study aimed to evaluate and associate the various side effects of COVID-19 vaccines at different covariate levels along with comorbid conditions. Methods: This cross-sectional study aimed to evaluate the side effects of COVID-19 vaccines in Bangladesh using data collected from a sample of vaccinated individuals through a structured questionnaire. The data were analyzed using descriptive statistics, bivariate analysis with a chi-square test, and multiple logistic regression model to identify the frequency, severity, and duration of side effects, as well as the associations between side effects and potential predictors. Our study investigated the side effects of four prominent approved COVID-19 vaccines in Bangladesh. Results: The findings revealed that Sinopharm was the most administered vaccine, accounting for 55% of the respondents. The majority of participants (38%) reported experiencing mild side effects, such as pain at the injection site, fatigue, and headache, while only 13% required hospitalization due to severe side effects. Significant associations were observed between vaccine type and variables such as gender, age group, concomitant health complications, prior COVID-19 history, physician's recommendation, and adverse consequences. Logistic regression analysis identified significant associations between the presence of side effects and variables such as concomitant health complications (OR=3.2 p-value: 0.011) and concomitant medications (OR=0.38, p-value: 0.039). Conclusion: These results provide valuable insights to help guide vaccination strategies and ensure vaccine safety in Bangladesh. Further investigation into these aspects in larger and more diverse groups is necessary, taking longitudinal follow-up and the objective evaluation of side effects into consideration.